PERUBAHAN BUNYI PADA BAHASA NIAS - siahaan, salman fauzan; Prayogo (Fakultas Bahasa dan Sastra Universitas PGRI Kanjuruhan Malang, 2025)
The Nias language has unique phonological characteristics, including open vowel patterns (almost all words end in vowels) and a rich grammatical system, such as the use of prefixes and suffixes to form words, this underlies the author's interest in studying the Nias language through comparative historical linguistics theory. This study aims to reveal what changes are found in the Nias language. This study uses a qualitative approach with recording and transcription techniques and then filters the data obtained. Informants who speak the Nias language are sources of Nias language data that meet the requirements of informants according to Comparative Historical Linguistics. The swadesh list contains vocabulary taken from speaker recordings. The results of this study found only four sound changes in the Nias language. There are four changes that occur in the sound position of the Proto Austronesian language into the Nias language, namely apheresis, syncope, apocope, and paragoge with apocope as the most changes found in this study. Keywords: Comparative Historical Linguistics, Sound Changes, Nias Language.